Determination of Liquefaction Hazard in Samarinda Using Fuzzy-GIS Method - Rachmadi, Ari; Septyandy, Muhammad Rizqy; Syam, Muhammad Amin (EL-JUGHRAFIYAH, 2024)
The phenomenon of liquefaction is the transformation of coarse-grained soil from a solid to a liquid state, resulting in a reduction in the bearing capacity of the soil due to an increase in hydrostatic pressure due to a sudden high cyclic load. Liquefaction usually occurs during an earthquake, where earthquake-triggering factors, ground acceleration, water table depth, overburden pressure, soil density, and soil type are used as input data. A fuzzy-GIS approach is used to combine these factors to map liquefaction potential. This method produced a preliminary map of liquefaction potential in Samarinda City. Validation of the Fuzzy-GIS model used field test data to assess liquefaction potential. The technique used in determining the liquefaction hazard zone in Samarinda is fuzzy-GIS processing with the results of field data calculations in CPT tests. The research results are accurate maps of the liquefaction hazard zone of the Samarinda region based on field data validation and Fuzzy-GIS analysis results. Based on the results of this research, the Samarinda area is divided into four zones of liquefaction hazard, ranging from very low to very low and medium to high. This research results in a map of potential liquefaction risk with more than 90% accuracy for prevention and mitigation in Samarinda City.